A New Cell Model for Investigating Prion Strain Selection and Adaptation - Alexandra Philiastides; Juan Manuel Ribes; Daniel Chun-Mun Yip; Christian Schmidt; Iryna Benilova; Peter-Christian Klöhn (Viruses, 2019)
Prion diseases are fatal neurodegenerative diseases that affect humans and animals. Prion strains, conformational variants of misfolded prion proteins, are associated with distinct clinical and pathological phenotypes. Host-strain interactions result in the selective damage of distinct brain areas and they are responsible for strain selection and/or adaptation, but the underlying molecular mechanisms are unknown. Prion strains can be distinguished by their cell tropism in vivo and in vitro, which suggests that susceptibility to distinct prion strains is determined by cellular factors. The neuroblastoma cell line PK1 is refractory to the prion strain Me7, but highly susceptible to RML. We challenged a large number of clonal PK1 lines with Me7 and successfully selected highly Me7-susceptible subclones (PME) to investigate whether the prion strain repertoire of PK1 can be expanded. Notably, the Me7-infected PME clones were more protease-resistant when compared to RML-infected PME clones, which suggested that cell-adapted Me7 and RML are distinct prion strains. Strikingly, Me7-refractory cells, including PK1 and astrocytes in cortico-hippocampal cultures, are highly susceptible to prions, being derived from homogenates of Me7-infected PME cells, suggesting that the passage of Me7 in PME cells leads to an extended host range. Thus, PME clones represent a compelling cell model for strain selection and adaptation.